2014
DOI: 10.2298/pif1404237t
|View full text |Cite
|
Sign up to set email alerts
|

Botrytis cinerea in raspberry in Serbia I: Morphological and molecular characterization

Abstract: SuMMaryMorphological and molecular characterisation of 130 isolates of Botrytis cinerea, derived from raspberry fruit originating from six commercial fields in a raspberry growing region of Serbia (locations: Požega, Prilike, Arilje, Ivanjica, Šabac and Valjevo) was performed. The results showed that all isolates formed white, uniform, aerial mycelia with entire margin on PDA medium. First morphological differences among the isolates appeared after six days of incubation. Three-week old isolates were grouped i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
8
0
2
Order By: Relevance
“…Moline and Upton (1987) stated that losses from the disease could be handled by swiftly cooling heads to below 5 oC following harvest and by storing 0 to 3 oC during marketing. (Elad and Stewart 2004, Esterio et al 2013, Hao et al 2017, Mor et al 2016, Rashid et al 2013, Tanović et al 2014, Uribe 2016 in the introduction part, due to thriving ability within a wide range of temperatures, the fungus can cause significant yield losses up to 100% in various agricultural crops. As regards globe artichoke, rots on heads of plants in the field may lead to considerable yield losses in globe artichoke production as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moline and Upton (1987) stated that losses from the disease could be handled by swiftly cooling heads to below 5 oC following harvest and by storing 0 to 3 oC during marketing. (Elad and Stewart 2004, Esterio et al 2013, Hao et al 2017, Mor et al 2016, Rashid et al 2013, Tanović et al 2014, Uribe 2016 in the introduction part, due to thriving ability within a wide range of temperatures, the fungus can cause significant yield losses up to 100% in various agricultural crops. As regards globe artichoke, rots on heads of plants in the field may lead to considerable yield losses in globe artichoke production as well.…”
Section: Resultsmentioning
confidence: 99%
“…As for Esterio et al (2013), they emphasized that postharvest loss from Botrytis rot was over 20% in blueberry production in Chile. Likewise, Tanović et al (2014) reported that Botrytis rot caused more than 50% yield losses in raspberry production particularly under wet and humid environmental conditions in pre-harvest in Serbia. The fungus also induced serious quantity and quality losses on susceptible varieties of grapevine (Elad and Stewart 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Morphometric, morphological and cultural characterization. The variables determined to the isolations were growth rate -calculated with growth at 48 h minus the growth of 24 h (Zhou et al, 2014), growth shape and color of mycelium, days to sporulation, days to formation of sclerotia, number of sclerotia, shape and color of sclerotia (Martínez et al, 2003, Tanovic et al, 2009, Tanovic et al, 2014. The sclerotia, conidia and conidiophores were measured (n=50) (Li et al, 2012) using an OLYMPUS BX 41 compound microscope with an OLIMPUS U-CMAD3 T2, U-TV1X-2 T2 camera (Tokyo, Japan) and the morphometry was carried out using the program ImageJ (Schindelin et al, 2015).…”
Section: Fully Bilingualmentioning
confidence: 99%
“…A total of 130 B. cinerea isolates, derived from diseased raspberry fruit collected at six locations in a major raspberry growing region in Serbia, identified based on their pathogenic and morphological characteristics and classified in two morphological and four genetic groups (Tanović et al, 2014), were used in this study (Tables 1 and 2). …”
Section: Fungal Isolatesmentioning
confidence: 99%
“…Thus, Martinez et al (2003Martinez et al ( , 2005 found vacuma isolates (without transposons) mostly to belong to the mycelial type and have a higher growth rate than transposa isolates (containing both transposons), while Giraud et al (1999) reported a difference in fungicide resistance frequencies in transposa and vacuma isolates. Our previous study (Tanović et al, 2014) revealed that all B. cinerea isolates originating from raspberry fields in Serbia belonged exclusively to the Group II genetic entity of B. cinerea described by Fournier et al (2003). The isolates were divided into two main morphological (mycelial and sclerotial) and four genetic groups (transposa, vacuma, boty and flipper).…”
Section: Introductionmentioning
confidence: 99%